1985
DOI: 10.1346/ccmn.1985.0330303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inorganic and Organic Ligands on the Formation of Aluminum Hydroxides and Oxyhydroxides

Abstract: Abstract--Hydroxide and oxyhydroxide products of aluminum were formed at room temperature at an initial AI concentration of 2 x 10 -3 M, pH 8.2, and at varying concentrations of organic and inorganic ligands commonly found in nature. The effectiveness of the ligands in promoting the formation of noncrystalline products over crystalline AI(OH)3 polymorphs was found to be in the following order: phthalate ~ succinate < glutamate < aspartate < oxalate < silicate -~ fluoride < phosphate < salicylate malate < tanna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 34 publications
2
47
0
2
Order By: Relevance
“…It is well known that amorphous aluminum hydroxide transforms into crystalline materials such as gibbsite, bayerite, nordstrandite or boehmite by prolonged aging, depending strongly on pH, temperature and concentration of organic and inorganic ligands present in solution (Barnhisel and Rich 1965;Hsu 1966Hsu , 1989Taylor 1987;Violante and Huang 1985, 1992. Gibbsite, bayerite and nordstrandite have a similar structure composed of basic sheets of close packed hydroxyls with A1 in octahedral co- ordination with different stacked sequences (Taylor 1987).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that amorphous aluminum hydroxide transforms into crystalline materials such as gibbsite, bayerite, nordstrandite or boehmite by prolonged aging, depending strongly on pH, temperature and concentration of organic and inorganic ligands present in solution (Barnhisel and Rich 1965;Hsu 1966Hsu , 1989Taylor 1987;Violante and Huang 1985, 1992. Gibbsite, bayerite and nordstrandite have a similar structure composed of basic sheets of close packed hydroxyls with A1 in octahedral co- ordination with different stacked sequences (Taylor 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Such fibrous boehmite is well known as "pseudoboehmite", whose disordered structure is caused by random intercalation of water molecules into the octahedral layers (Tettenhorst and Hofmann 1980). Similar material can be easily produced by aging of amorphous Al-hydroxide prepared by neutralization of acidic solution containing A1 ions (Souza-Santos et al 1953;Violante and Huang 1985;Violante et al 1993).…”
Section: Reaction Products In Naoh Solutions At 200 ~mentioning
confidence: 99%
“…This order generally corresponded to the results obtained by Kato (1977). According to Violante and Huang (1985), the capability of organic acids to solubilize A1 oxides was controlled by their chelating power for A1, or stability constants. It was demonstrated that stability constants of A1 complexes decreased in the following order: citrate>oxalate>tartrate>>acetate (Martell and Calvin 1956;Earl et al 1979).…”
Section: Effect Of Extracting Solution On Free Oxide Removal and Chanmentioning
confidence: 99%